1993
DOI: 10.1007/bf01991124
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of calcitonin gene-related peptide (CGRP) to neurogenic vasodilator responses

Abstract: The neuropeptide calcitonin gene-related peptide (CGRP) is a potent vasodilator in the microcirculation of many tissues including the skin and joint. In order to elucidate the mechanism of endogenous CGRP release, we have used a multiple site 133Xe clearance technique to measure local blood flow changes in response to agents injected intradermally in the rabbit. Capsaicin (100 nmol/site) and human alpha CGRP (3 pmol/site) stimulated similar increases in blood flow and, in both cases, the effect was totally abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…The residual vasodilatation seen in capsaicin-pretreated rats is likely to be a reaction to the injection per se, since it was not higher than the vasodilatation caused by intraplantar injection of saline alone. These findings are consistent with the notion that the capsaicin-induced rise of cutaneous blood flow is mediated by stimulation of fine afferent nerve fibres (Holzer, 1992) and release of the vasodilator transmitter CGRP (Hughes and Brain, 1991;Brain et al, 1993). Hence, the absence of any effect of interleukin-lß in capsaicin-pretreated rats implies that the cytokine augments the neurogenic component in the vasodilator response to capsaicin by sensitizing afferent nerve fibres to noxious stimuli.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The residual vasodilatation seen in capsaicin-pretreated rats is likely to be a reaction to the injection per se, since it was not higher than the vasodilatation caused by intraplantar injection of saline alone. These findings are consistent with the notion that the capsaicin-induced rise of cutaneous blood flow is mediated by stimulation of fine afferent nerve fibres (Holzer, 1992) and release of the vasodilator transmitter CGRP (Hughes and Brain, 1991;Brain et al, 1993). Hence, the absence of any effect of interleukin-lß in capsaicin-pretreated rats implies that the cytokine augments the neurogenic component in the vasodilator response to capsaicin by sensitizing afferent nerve fibres to noxious stimuli.…”
Section: Discussionsupporting
confidence: 89%
“…The use of s.c. N°-nitro-L-arginine methyl ester was regarded as impractible, therefore, given that local N°-nitro-L-arginine methyl ester could inhibit vasodilator responses solely by virtue of its vasoconstrictor effect. Such a functional antagonism might be responsible for the inhibitory effect of topical N°-nitro-L-arginine methyl ester on capsaicin-induced vasodilatation (Brain et al, 1993), an effect that was not observed after i.v. administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macmillan Press Ltd, 1994 Preliminary findings of this study have been published in the proceedings of the European Workshop on Inflammation Meeting, London, 1992 (Brain et al, 1993).…”
Section: Introductionmentioning
confidence: 87%
“…Of specific interest is that a portion of the skin blood flow response to innocuous heating is blunted by blocking the TRPV1 ion channel with capsazepine (Wong and Fieger, 2010). The increase in skin blood flow via TRPV1 ion channels is consistent with the activation of an axon-reflex and the release of vasoactive neuropeptides, presumably calcitonin gene-related peptide (CGRP) and Substance P (Brain and Williams, 1988; Brain et al, 1993). Both TRPV1 and TRPM3, when activated by a ligand (capsaicin and neurosteriod pregnenolone, respectively) produce an axon reflex mediated release of CGRP (Brain et al, 1986; Holzer, 1991; Tominaga and Caterina, 2004; Held et al, 2015).…”
Section: Introductionmentioning
confidence: 75%